2006
DOI: 10.1080/09593332708618619
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Divalent Copper, Zinc, Cadmium and Lead Ions from Aqueous Solution by Waste Tea and Coffee Adsorbents

Abstract: The adsorption of the divalent cations of Cu, Zn, Cd and Pb by tea leaves and coffee grounds from aqueous solutions is described. Both adsorbents exhibited strong affinity for these ions which could be described by a simple single-site equilibrium model. For coffee, the order of increasing adsorption equilibrium constant K was Cu < Pb < Zn < Cd, while for tea the opposite order was observed indicating that the adsorption sites on each adsorbent have a different chemical nature. Adsorption decreased at low pH <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 0 publications
2
35
1
Order By: Relevance
“…Results showed that protocatechuic acid was the weakest chelator (1.43 M −1 ), followed by hydroxytyrosol (2.66 M −1 ), gallic acid (4.78 M −1 ), caffeic acid (8.12 M −1 ) and chlorogenic acid (20.13 M −1 ). The adsorption of divalent cations of Cu, Zn, Cd and Pb by coffee grounds and tea leaves from aqueous solutions was described by Utomo and Hunter (2006). Both materials exhibited strong affinity for these ions, which could be described by a simple single-site equilibrium model.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that protocatechuic acid was the weakest chelator (1.43 M −1 ), followed by hydroxytyrosol (2.66 M −1 ), gallic acid (4.78 M −1 ), caffeic acid (8.12 M −1 ) and chlorogenic acid (20.13 M −1 ). The adsorption of divalent cations of Cu, Zn, Cd and Pb by coffee grounds and tea leaves from aqueous solutions was described by Utomo and Hunter (2006). Both materials exhibited strong affinity for these ions, which could be described by a simple single-site equilibrium model.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some studies have highlighted the possibility of using SCG to remove basic dyes (Franca et al, 2009) or heavy metal ions (Tokimoto et al, 2005;Utomo and Hunter, 2006;Zuorro and Lavecchia, 2010) from contaminated waters. For metal ions, the order of adsorption capacity was Cd 2þ gt; Zn 2þ gt; Pb 2þ gt; Cu 2 and the effectiveness of metal removal was higher between pH values of 4 and 10 (Utomo and Hunter, 2006). These properties seem to be closely related to the presence of phenolic compounds with metalchelating properties and to the protein content.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have reported the use of coffee by-products to remove either organic (Boonamnuayvitaya et al 2004;Oliveira et al 2008) or inorganic (Utomo and Hunter 2006) pollutants from water.…”
Section: Introductionmentioning
confidence: 99%